Influencia de los movimientos oculares y su relación en la comprensión de la lectura (2022)
Reading is one of the first school goals at an early age and an adequate adaptive process to school life will depend on reading fluency and comprehension, which is why it is necessary to develop visual, motor and cognitive skills.